Multi-component cash transfer programs: Evidence from Mali’s social safety net program (Jigisémèjiri) - Hidrobo, Melissa; Huybregts, Lieven; Karachiwalla, Naureen; Roy, Shalini (International Food Policy Research Institute, 2020)
Despite falling rates of poverty and child undernutrition in Africa over the last two decades, the absolute number of people living in poverty and the absolute number of undernourished children continue to rise due to population growth (Beegle et al., 2018; Black et al., 2013). Global evidence suggests that cash transfer programs can reduce poverty and food insecurity and can build resilience for the poor. When cash transfer programs are com-bined with nutrition interventions, they also have the potential to accelerate improvements in child nutrition, especially when targeted to the critical window of opportunity for nutrition, the first one thousand days of a child’s life (Ruel et al., 2013). In West Africa, many cash transfer programs are combined with accompanying measures such as promotion sessions that aim to improve knowledge and increase adoption of recommended behaviors—including those related to child nutrition (Beegle et al., 2018, see Box 1). However, the extent to which such multi-component programs lead to changes in behavior and improve-ments in outcomes related to children’s nutrition and health is still not well-understood.